Metastable intermetallic phases in the Al-Sm system. (December 2019) - Zhou, S.H.; Meng, F.Q.; Kramer, M.J.; Ott, R.T.; Zhang, F.; Ye, Z.; Jain, S.; Napolitano, R.E.
Highlights: Amorphous alloys provide a means for investigating the relative stability of metastable phases. Experiments and first principles calculations are used for modeling the energetic landscape involving metastable intermetallics. In situ high energy diffraction is used to resolve complex multi-stage transformation sequences. Abstract: The thermodynamic landscape involving several metastable phases in the glass-forming Al-Sm system is assessed, integrating experimental measurements and first principles calculations into a comprehensive CALPHAD description. The phases examined here include Al41 Sm5 -η, Al60 Sm11 -ε, Al5 Sm-θ, Al5 Sm-π and Al4 Sm-γ, having basis stoichiometries from 9 to 20 at% Sm, a range over which the Al-fcc and Al3 Sm phases are stable. Amongst the metastable phases examined, our findings indicate that the Al41 Sm5 -η and Al60 Sm11 -ε phases comprise the convex hull of minimum formation energies at absolute zero. Competitive crystallization processes were investigated through situ X-ray diffraction and differential scanning calorimetry and used to assess relative stability within the overall landscape. Asserting thermodynamic scenarios consistent with our measurements, temperature-dependent Gibbs free energies for the metastable phases are proposed along with the corresponding constrained phase diagrams, comprehensively showing metastable phases and associated invariant reactions. Assumptions and limitations of the proposed thermodynamic model are discussed with reference to available transport data.